REKONSTRUKSI PEMIKIRAN FIKIH IMAM AL-HARAMAIN MELALUI KITAB NIHAYAH AL-MATLAB - Ahmad Syauky; Warul Walidin (Yayasan An-Nur Meunara Baro, 2025)
Imam al-Haramain al-Juwaini is widely recognized as one of the foremost intellectual figures in Islamic legal history, particularly for his contributions to the development of usul al-fiqh and the refinement of the Shafi‘i school. His magnum opus, Nihayah al-Matlab fi Dirayah al-Madhhab, is not merely a compilation of classical legal opinions, but a systematic reconstruction of legal methodology that integrates textual sources (nusus), rational reasoning (‘aql), and the objectives of Islamic law (maqasid al-shari‘ah). This article aims to examine and reconstruct al-Juwaini’s legal thought using a qualitative approach based on library research and textual analysis of both primary and secondary sources. The study employs content analysis to explore the methodological structure, legal reasoning, and contemporary relevance of al-Juwaini’s jurisprudential model. The findings reveal that al-Juwaini succeeded in establishing a dynamic yet principled legal framework rooted in the authority of divine revelation. He harmonized Ash‘arite theology with rational jurisprudence and employed tools such as analogy (qiyas), public interest (maslahah), and maqasid to address complex and disputed legal issues. His thought reflects not only the preservation of the Shafi‘i legacy but also its renewal through critical engagement with evolving social realities. This reconstruction demonstrates that al-Juwaini was both a transmitter and a reformer, whose intellectual legacy offers a valuable foundation for reviving contextual ijtihad in the modern era. Therefore, Nihayah al-Matlab should be regarded as a strategic reference for scholars seeking to develop an adaptive and principled Islamic legal system responsive to contemporary challenges.